HUBUNGAN FINANCIAL DISTRESS & MEKANISME GCG TERHADAP PELAPORAN AUDIT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005-2010 - Mario Pratama Putra Riyanda; Susi Indriani (Fakultas Ekonomi Universitas Negeri Jakarta, 2013)
Abstract This study examines the relation between the composition of financially distressed banks, boards of director Committees and institusional ownership to the likelihood of receiving going concern reports. The composition board of director Committees and institusional ownership represent Good Corporate Governance (GCG) mechanism in banks. Financial firms were highly regulated, so we combine bapepam regulation and altman Z score to identify banks that fit for the financial distress category. For banks experiencing financial distress during 2005-2010, by using logistic regression we find that the greater percentage of financial distress in banks, the smaller the probability the Auditor will issue a going concern report. This empirical study did not support role GCG mechanism on Audit reporting. These results can give us a little sight about implementation of GCG in Indonesia specialy for financial firm. The contribution will go to support regulators’ concern about financial reporting, firms behavior (financiall and non financial firms) in making healthy environment with GCG and the need of balancing proportion in ownership structure in form of the composition board committee and institusional ownership to minimize moral hazard . Keywords : financial distress, board of director Committees, institusional ownership and going concern reports